Problematic Online Video Watching, Boredom Proneness and Loneliness Among First-Year Chinese Undergraduates: A Two-Wave Longitudinal Study - Yan Z; Yang Z; Xu X; Zhou C; Sang Q (Psychology Research and Behavior Management)
Zhihao Yan,1,* Zeyang Yang,2,* Xinyuan Xu,3 Chengjun Zhou,2 Qingsong Sang1 1School of Educational Science, Anhui Normal University, Wuhu, People’s Republic of China; 2Department of Psychology, School of Education, Soochow University, Suzhou, People’s Republic of China; 3Foreign Language College, Shanghai Normal University, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qingsong Sang, School of Educational Science, Anhui Normal University, Wuhu, People’s Republic of China, Tel +86 13956186006, Email s7210qs1@ahnu.edu.cn Chengjun Zhou, Department of Psychology, School of Education, Soochow University, Suzhou, People’s Republic of China, Tel +86 13057471246, Email zhouchengjun@suda.edu.cnPurpose: While previous cross-sectional studies have investigated the relationship between problematic online video watching and mental health issues, longitudinal studies exploring their bidirectional relationship remain relatively scarce. This study aimed to fill this gap by conducting a two-wave longitudinal design.Participants and Methods: Six hundred and ninety-nine first-year undergraduates voluntarily completed two rounds of questionnaire surveys assessing problematic online video watching, boredom proneness and loneliness with an interval of 4 months. To test the research hypotheses, cross-lagged panel models were performed using AMOS 24.0.Results: Our results revealed the that (1) Boredom proneness and problematic online video watching were mutually influenced. (2) Loneliness at T1 positively predicted the level of problematic online video watching at T2 but not vice versa. (3) Boredom proneness mediated the link between loneliness and problematic online video watching. (4) Chinese first-year undergraduates’ levels of problematic online video watching and boredom proneness significantly increased during their educational transition period from high school to university.Conclusion: The present study enhances our understanding of the dynamic relationships between problematic online video watching, boredom proneness and loneliness, highlighting the targeted prevention and interventions for first-year undergraduates.Keywords: problematic online video watching, boredom proneness, loneliness, cross-lagged panel model